Noise Induced Hearing Loss (NIHL) Effect among Workers in Small Medium Enterprises (SME) in Malaysia - T.X. Rong; M.H. Hassim; M.Z.B. Abdul Halim (Chemical Engineering Transactions, 2017)
A cross-sectional study of noise-induced hearing loss (NIHL) due to occupational noise exposure of greater than 90 dB (A) was conducted among Small Medium Enterprise (SMEs) workers throughout Malaysia. Area noise monitoring was carried out to determine the high risk area exposed to noise. Personal noise monitoring was conducted among the exposed workers. Questionnaire on demographic information including medical history was obtained. The secondary data on individual audiometric assessment was obtained from 18 SMEs. There are 5 out of 18 SMEs in this project with the measured area noise level greater than 90 dB(A) - this is not in compliance with the Factories and Machinery Act 1967 (Noise Regulation 1989). This study revealed that there was a significant correlation (r = 0.469, p = 0.003) between area noise monitoring and personal noise monitoring. Furthermore, there were complaints on sudden hearing loss, ear pain and ringing sound in ears received from the workers.